pH-Dependent single-step rapid synthesis of cuo and cu2o nanoparticles from the same precursor - Nikam, Arun V.; Arulkashmir, Arulraj; Krishnamoorthy, Kothandam; Kulkarni, Amol A.; Bhagavatula L. V. Prasad (Crystal Growth & Design, 2014)
A single-step protocol to prepare Cu2O and CuO nanocrystalline particles from the same precursor by microwave irradiation has been developed using the pH of the solution as the only variable parameter. The utility of different bivalent Cu-precursors for synthesis of CuO and Cu2O nanoparticles was also investigated. The morphology, phase purity, and optical properties of these nanoparticles were analyzed using TEM, SEM, XRD, and optical spectroscopy. The band edges were determined using cyclic voltammetry. Field effect transistors based on CuO nanoparticles showed a hole mobility of 3.5 x 10(-2) cm(2) V-1 s(-1), making them a suitable candidate for energy-related applications. The effect of hydrazine vapor exposure on the IV-characteristics of CuO nanoparticles was also investigated. This revealed a decrease in source current with respect to time.

Phenols from green tea as a dual functional coating to prepare devices for energy storage and molecular separation - Das, Chayanika; Jain, Bhanprakash; Krishnamoorthy, Kothandam (Chemical Communications, 2015)
Polyphenols from green tea were used to electrolessly deposit gold on silk cocoons (SCs) and nanoporous aluminum oxide (AAO) templates. The gold coated cocoons were used as electrodes in supercapacitors and showed a capacitance as high as 254 F g(-1) and a specific power of 2287 W kg(-1). A metal coated AAO template was used for molecular separation.

Polymer and graphene layer to increase dye regeneration and suppress back electron transfer in dye sensitized solar cells - Sudhakar, Vediappan; Arulkashmir, Arulraj; Krishnamoorthy, Kothandam (Chemical Communications, 2017)
Dye regeneration was improved by using an optimum quantity of graphene, which was dispersed in a polymer that suppresses back electron transfer. Using this approach, DSSCs with an efficiency of 10.4% have been fabricated.

Polyvalent interaction and confinement to suppress polysulfide dissolution and improve electrocatalysis - Bharathkumar, H. J.; Shivankar, Bhavana R.; Krishnamurty, Sailaja; Chen, Dehong; Caruso, Rachel A.; Krishnamoorthy, Kothandam (CATALYSIS SCIENCE & TECHNOLOGY, 2024)
Keywords: cathode material; HIGH-CAPACITY; Particles; SULFUR CATHODE